N-methyl-D-aspartate channel and consciousness: From signal coincidence detection to quantum computing - Freitas da Rocha, Armando; Pereira Jr., Alfredo [UNESP]; Bezerra Coutinho, Francisco Antonio (Elsevier, 2001)
Research on Blindsight, Neglect/Extinction and Phantom limb syndromes, as well as electrical measurements of mammalian brain activity, have suggested the dependence of vivid perception on both incoming sensory information at primary sensory cortex and reentrant information from associative cortex. Coherence between incoming and reentrant signals seems to be a necessary condition for (conscious) perception. General reticular activating system and local electrical synchronization are some of the tools used by the brain to establish coarse coherence at the sensory cortex, upon which biochemical processes are coordinated. Besides electrical synchrony and chemical modulation at the synapse, a central mechanism supporting such a coherence is the N-methyl-D-aspartate channel, working as a 'coincidence detector' for an incoming signal causing the depolarization necessary to remove Mg 2+, and reentrant information releasing the glutamate that finally prompts Ca 2+ entry. We propose that a signal transduction pathway activated by Ca 2+ entry into cortical neurons is in charge of triggering a quantum computational process that accelerates inter-neuronal communication, thus solving systemic conflict and supporting the unity of consciousness. © 2001 Elsevier Science Ltd.
Keywords: calcium ion; glutamic acid; magnesium ion; n methyl dextro aspartic acid; association cortex; brain cell; brain function; calcium cell level; calcium transport; channel gating; consciousness; human; mathematical model; membrane depolarization; nerve cell network; perception; priority journal; sensory cortex; signal transduction; synaptic transmission; Animals; Calcium; Cerebral Cortex; Consciousness; Glutamic Acid; Humans; Magnesium; Models, Biological; Nerve Net; Perception; Pyramidal Cells; Receptors, N-Methyl-D-Aspartate; Signal Transduction